Role of human immunodeficiency virus and cytomegalovirus in AIDS encephalitis. - Wiley, C. A. (1988)
Approximately half of patients with advanced acquired immune deficiency syndrome (AIDS) develop a subcortical dementia. The brains of all autopsies on AIDS patients performed at UCSD between 1982 and 1986 (N = 93) were studied. Neuropathologic changes consistent with a viral encephalitis were present in 54 brains (58%). Human immunodeficiency virus (HIV) antigens were detected in 37 of the brains (40%), most frequently in macrophages, multinucleated giant cells, and endothelial cells. Cytomegalovirus (CMV) was detected in 31 of the brains (33%), 22 of which also contained HIV. Cellular localization of CMV antigens suggests that CMV disseminates to the central nervous system hematogenously where the virus can infect endothelial cells, glia, and neurons. While the temporal course of the appearance of these two viruses within the CNS is not clear, the common simultaneous occurrence of both viruses within the brains of AIDS patients suggests that in vivo interaction between them may play a role in the pathogenesis of AIDS-associated encephalitis. Given the significant neurologic symptoms described in AIDS patients, the paucity of viral antigens suggests a pathogenic mechanism of indirect CNS damage rather than direct viral infection.